In Vitro Evaluation of Hyperthermia Magnetic Technique Indicating the Best Strategy for Internalization of Magnetic Nanoparticles Applied in Glioblastoma Tumor Cells - Javier B. Mamani; Taylla K. F. Souza; Mariana P. Nucci; Fernando A. Oliveira; Leopoldo P. Nucci; Arielly H. Alves; Gabriel N. A. Rego; Luciana Marti; Lionel F. Gamarra (MDPI AG, 2021)
This in vitro study aims to evaluate the magnetic hyperthermia (MHT) technique and the best strategy for internalization of magnetic nanoparticles coated with aminosilane (SPIONAmine) in glioblastoma tumor cells. SPIONAmine of 50 and 100 nm were used for specific absorption rate (SAR) analysis, performing the MHT with intensities of 50, 150, and 300 Gauss and frequencies varying between 305 and 557 kHz. The internalization strategy was performed using 100, 200, and 300 µgFe/mL of SPIONAmine, with or without Poly-L-Lysine (PLL) and filter, and with or without static or dynamic magnet field. The cell viability was evaluated after determination of MHT best condition of SPIONAmine internalization. The maximum SAR values of SPIONAmine (50 nm) and SPIONAmine (100 nm) identified were 184.41 W/g and 337.83 W/g, respectively, using a frequency of 557 kHz and intensity of 300 Gauss (≈23.93 kA/m). The best internalization strategy was 100 µgFe/mL of SPIONAmine (100 nm) using PLL with filter and dynamic magnet field, submitted to MHT for 40 min at 44 °C. This condition displayed 70.0% decreased in cell viability by flow cytometry and 68.1% by BLI. We can conclude that our study is promising as an antitumor treatment, based on intra- and extracellular MHT effects. The optimization of the nanoparticles internalization process associated with their magnetic characteristics potentiates the extracellular acute and late intracellular effect of MHT achieving greater efficiency in the therapeutic process.